International financing of economic development : proceedings of the World Scientific Banking Meeting, Dubrovnik, Oct. 31-Nov. 5, 1977 - World Scientific Banking Meeting; Negoslav, Ostojic (Beograd, Nemanjina: Administration for international Scientific, Educational, Cultural and Technical Corporation, 1977)
The book is the proceedings of conference on international financing of economic development, organized by the World Scientific Banking Meeting. The papers examines the problems associated with the international financing of development particularly among the developing countries.
Translated from the original title.
includes bibliographical footnotes
usc 14/7/17
Loans
Keywords: International finance; Economic development; Developing countries